2018
DOI: 10.2147/idr.s175967
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant <em>Staphylococcus aureus</em>: livestock-associated, antimicrobial, and heavy metal resistance

Abstract: Staphylococcus aureus is an opportunistic pathogen of human and other mammals that is of increasing clinical and veterinary importance due to its ability to rapidly develop antimicrobial resistance. The injudicious use of antibiotics has given rise to the emergence of antibiotic resistant S. aureus strains, most importantly methicillin-resistant Staphylococcus aureus (MRSA). The emergence of livestock-associated MRSA (LA-MRSA) has highlighted the importance of directed research toward its prevention, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 127 publications
4
72
0
2
Order By: Relevance
“…61 In addition, imprudent use of antibiotics in livestock farms was recently reported in South Africa. 62 The findings in the current study were in line with other studies which reported high resistance rates towards ampicillin, tetracycline, trimethoprim-sulfamethoxazole. [63][64][65] Higher resistance rates against azithromycin (16.9%) and ceftriaxone (24.07%) were previously reported 66 as compared to the current study.…”
Section: Discussionsupporting
confidence: 92%
“…61 In addition, imprudent use of antibiotics in livestock farms was recently reported in South Africa. 62 The findings in the current study were in line with other studies which reported high resistance rates towards ampicillin, tetracycline, trimethoprim-sulfamethoxazole. [63][64][65] Higher resistance rates against azithromycin (16.9%) and ceftriaxone (24.07%) were previously reported 66 as compared to the current study.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, some studies investigating the distribution of S. aureus in different ecological niches from livestock in Algeria [27,28] reported prevalence rates that are ranging from 18% to 53%f or S. aureus and 5.4% to 7.6% for MRSA. Moreover, a recent study conducted by Dweba et al [13], in South African livestock production systems identi ed MRSA isolates in 27% with a signi cant relationship (p < 0.001) with the animal host.…”
Section: Discussionmentioning
confidence: 96%
“…The emergence of LA-MRSA has also been increasingly associated with alarming rates of MRSA infection and colonization among humans in contact with livestock, suggesting an increased risk of zoonotic transmission [9,10]. These pathogenic strains could be subsequently dispersed to the environment and to other species [7] through food chain [11] and direct contact [12,13,14]. Numerous studies have indicated that the increasing rate of the incidence of antimicrobial resistance in S. aureus in animals is a result of the misuse and unjusti ed utilization of antibiotics [11,14,15] in animal husbandry either, for therapeutic, preventive purposes or as growth promoters (GPs).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of mecC MRSA are presently uncommon and have been restricted to Europe; however, mecC MRSA represent a potential diagnostic problem due to the reliance on mecA or PBP2a/2′ detection for MRSA diagnosis (Paterson et al, 2014). Hence, livestock and livestock production systems have been reported to act as potential reservoirs for the emergence of new MRSA clones with the capacity to cross the species barrier and endure host-adaptive evolution, showing potential to become established in human populations worldwide as successful epidemic lineages (Spoor et al, 2013;Dweba et al, 2018). However, among the 195 cattle, 63 human and 83 environmental samples recovered from the 12 different farms included in this study and only one human sample was positive for presumptive MRSA colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is a robust and versatile opportunistic pathogen that can survive in a diversity of environments (Sergelidis and Angelidis, 2017). It is frequently present in the natural flora of the nose and skin of both humans and animals, being also isolated from foods, food production systems and the environment, causing a range of illnesses from minor skin infections and food poisoning to life-threatening diseases (Cuny et al, 2015;Dweba et al, 2018;Gajdács, 2019). Methicillin-resistant Staphylococcus aureus (MRSA) is considered the first representative of multidrug-resistant bacteria and currently represents a global burden since it is resistant to almost all beta-lactams and can also show resistance to other major antimicrobial classes such as the fluoroquinolones (Gajdács, 2019).…”
Section: Introductionmentioning
confidence: 99%